Integration of distributed generation and compensating capacitor in radial distribution system via firefly algorithm - N. Khuan; S. R. A. Rahim; M. H. Hussain; A. Azmi; S. A. Azmi (Institute of Advanced Engineering and Science, 2019)
This paper presents an integration of distributed generation and capacitor in radial distribution system via Firefly Algorithm (FA). In this study, the FA is developed in order to determine the optimal location and size for compensation schemes namely distributed generation (DG) and compensating capacitor (CC). The FA which is a meta-heuristic algorithm is inspired by the flashing behavior of fireflies. The proposed technique was tested on IEEE Reliability Test systems namely the IEEE 69-bus and the program was developed using the MATLAB programming software. The results shown a significant reduction in the line losses and voltage profile improvement has been obtained with the installation of distributed generation and capacitor in the system.